Carbon-coated oxide coating on surface of titanium material as well as preparation method and application of carbon-coated oxide coating

By generating a carbon-encapsulated oxide coating on the surface of titanium material, Ti-O ion bonds are generated using organic carboxylic acid ligands and defect sites of titanium material, and forming metal organic framework materials at high temperatures, the titanium material is solved in hydrogen-water The problem of insufficient corrosion and bonding strength in the conversion system has achieved efficient and durable coating preparation.

CN119194420AActive Publication Date: 2024-12-27WESTERN METAL MATERIAL
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411300753.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing surface coating of titanium materials is easily corroded in hydrogen-water conversion systems with high acidity, high humidity and high temperature, resulting in an increase in interface contact resistance. It is difficult for traditional deposition technology to achieve high binding strength and durability, carbon materials and titanium materials. The low matching degree of the lattice and thermal expansion coefficient leads to frequent coating peeling.

Method used

The titanium material is treated with inorganic acid to form defect-rich surfaces, and Ti-O ion bonds are generated using organic carboxylic acid ligands and defect sites of titanium material. Then, it reacts at 80°C to 150°C to form a metal organic framework material, and then carbonization and oxidation are carried out through annealing. The treatment forms a carbon-encapsulated oxide coating that closely combines with the titanium substrate to improve adhesion and corrosion resistance.

Benefits of technology

A carbon-encapsulated oxide coating with high uniformity, high bonding strength and corrosion resistance on the surface of titanium material is achieved, which improves the durability and conductive properties of the coating, avoids the coating shedding and cracking, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194420A_ABST
    Figure CN119194420A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal surface coating preparation, in particular to a titanium material surface carbon-coated oxide coating and a preparation method and application thereof.The preparation method comprises the following steps that an organic carboxylic acid ligand is dissolved in a solvent, and a defect-rich titanium material is added for adsorption; and adding a metal ligand into the system for reaction, and performing annealing carbonization and oxidation treatment after the reaction to obtain the titanium material with the carbon-coated oxide coating. Based on a coordination nucleation mode, a metal organic framework material is used as a carbon source, a defect site on the surface of titanium is used as a nucleation center, and a coating material precursor grows in situ. Through annealing carbonization and oxidation treatment, a tightly combined carbon-coated oxide coating material is obtained, and the coating is high in winding plating property, uniformity and bonding strength and has high conductivity and high corrosion resistance. The preparation scheme is low in cost and high in synthesis efficiency, and the carbon-coated oxide coating can be used for surface protection of a titanium-based bipolar plate and a diffusion layer component in proton exchange membrane electrolyzed water and hydrogen fuel cell equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface coating preparation, and in particular to a carbon-wrapped oxide coating on the surface of a titanium material, a preparation method and an application thereof. Background Art

[0002] In the hydrogen-water conversion system, water electrolysis technology and hydrogen fuel cell technology are considered to be important development directions for green and low-carbon hydrogen production and use in the future. Bipolar plates and diffusion layers are key components in proton exchange membrane water electrolysis (PEMWE) and hydrogen fuel cell (PEMFC) equipment. The operating conditions of PEMWE and PEMFC equipment are relatively harsh, generally characterized by high acidity, high humidity and high temperature. Therefore, high requirements are placed on the conductivity and corrosion resistance of bipolar plate and diffusion layer materials. Titanium metal materials are an ideal material for bipolar plates and diffusion layers due to their high corrosion resistance, good mechanical strength, high volume power and high specific energy density. However, titanium metal materials will be oxidized during use to form a low-conductivity passivation film, which leads to high interface contact resistance and increased ohmic loss. Generally, an effective measure is to prepare a highly conductive and corrosion-resistant coating such as pure metal, nitride, carbide, etc. on the titanium surface. Carbon materials are widely used as surface protective coating materials for metal bipolar plates and diffusion layers due to their low cost and excellent conductivity and corrosion resistance.

[0003] At present, the mainstream coating preparation technologies mainly include physical vapor deposition and chemical vapor deposition. However, due to the low lattice matching and thermal expansion coefficient matching between carbon materials and metal materials, the bonding strength between carbon materials and base metal materials is usually low, and the coating will fall off after long-term use. When solving the bonding strength problem of materials, traditional deposition technology mainly includes two technologies: one is to use heterogeneous structure epitaxial growth technology, using lattice matching to reduce lattice distortion and defects caused by lattice constant mismatch, and improve the matching degree between materials to improve adhesion; the other is to match the thermal expansion coefficients of different materials to reduce the overall thermal expansion difference of the coating, so as to reduce stress and deformation and ensure the stability of the structure. These traditional deposition technologies often require step-by-step matching of different materials to form a multi-component, multi-level coating structure, but there are still differences in lattice structure and thermal expansion coefficient between different materials, and it is inevitable to increase the coating thickness and process steps. Efficient and convenient strong bonding coating preparation technology has always been an urgent problem to be solved in the field of protective coatings for PEMWE and PEMFC equipment components. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a carbon-wrapped oxide coating on the surface of a titanium material and a preparation method and application thereof. The present invention obtains a carbon-wrapped oxide coating with high uniformity, high bonding strength, corrosion resistance and high conductivity on the surface of the titanium material. The obtained carbon-wrapped oxide coating is used for the surface of titanium-based bipolar plates and diffusion layers of PEMWE and PEMFC equipment, which can effectively prevent titanium metal corrosion and improve the durability of the coating. The preparation method is simple and convenient.

[0005] The mechanism of coating preparation of the present invention is as follows Figure 1 As shown, the metal organic framework material is used as the carbon source. Based on the high matching of similar materials, the highly reactive defect sites on the surface of the titanium material are utilized as the nucleation center in the organic titanium metal framework, which reacts rapidly with the organic carboxylic acid ligands to generate strongly bound Ti-O ionic bonds, and then the organic metal framework material is grown in situ, and then annealing is performed to form a carbon-wrapped oxide coating material.

[0006] The present invention is achieved through the following solutions.

[0007] The first object of the present invention is to provide a method for preparing a carbon-coated oxide coating on the surface of a titanium material, comprising the following steps:

[0008] The titanium material is treated with an inorganic acid solution to obtain a defect-rich titanium material.

[0009] The organic carboxylic acid ligand, anhydrous methanol and N,N-dimethylformamide are uniformly mixed and added to the defect-rich titanium material for adsorption, so that the organic carboxylic acid ligand forms a Ti-O ion bond with the defect sites in the titanium material.

[0010] Then, a metal ligand titanium isopropoxide is added into the system and reacted at 80°C to 150°C. During the reaction, titanium isopropoxide and organic carboxylic acid ligands in situ grow metal organic framework materials on the surface of the titanium material to form a titanium material loaded with a metal organic framework material coating.

[0011] The titanium material loaded with the metal organic framework material coating is subjected to annealing, carbonization and oxidation treatment to obtain a carbon-wrapped oxide coating on the surface of the titanium material.

[0012] In a preferred embodiment of the present invention, the organic carboxylic acid ligand is one of terephthalic acid, 2-aminoterephthalic acid, 2,5-dihydroxyterephthalic acid and 3,3',5,5'-tetracarboxydiphenylmethane.

[0013] In a preferred embodiment of the present invention, the molar ratio of the organic carboxylic acid ligand, anhydrous methanol and N,N-dimethylformamide is 1:10-20:20-40.

[0014] In a preferred embodiment of the present invention, the molar ratio of titanium isopropoxide to the organic carboxylic acid ligand is 0.5-1:1.

[0015] In a preferred embodiment of the present invention, the reaction time is 10 h to 100 h.

[0016] In a preferred embodiment of the present invention, the annealing carbonization and oxidation treatment are carried out in a muffle furnace in an air atmosphere at a temperature of 200° C. to 800° C. and a holding time of 10 min to 120 min.

[0017] In a preferred embodiment of the present invention, the titanium material is immersed in an inorganic acid solution and then rinsed with water to obtain a defect-rich titanium material; the temperature is 70° C. to 100° C. and the immersion time is 1 min to 30 min.

[0018] In a preferred embodiment of the present invention, the inorganic acid solution is selected from one of 0.5wt% hydrochloric acid, 5wt% sulfuric acid, 85wt% phosphoric acid, 5wt% hydrofluoric acid and 5wt% to 20wt% oxalic acid.

[0019] In a preferred embodiment of the present invention, the titanium material includes titanium foil, plate and products.

[0020] The second object of the present invention is to provide a carbon-wrapped oxide coating on the surface of a titanium material prepared by the above preparation method.

[0021] The third object of the present invention is to provide the application of the carbon-wrapped oxide coating on the surface of the titanium material in the protection of proton exchange membrane water electrolysis and hydrogen fuel cell equipment.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The invention firstly treats a titanium material with an inorganic acid to obtain a defect-rich titanium material; then, the defect-rich titanium material is immersed in a solution containing an organic carboxylic acid ligand, so that the defect-rich titanium material adsorbs the organic carboxylic acid ligand, and the organic carboxylic acid ligand generates a Ti-O ion bond with a defect site in the titanium material, wherein the solvent is made of anhydrous methanol and N, N-dimethylformamide, the anhydrous methanol can stabilize the organic carboxylic acid ligand, and can regulate the balance between subsequent nucleation and growth of a metal organic framework, and the N, N-dimethylformamide is subsequently decomposed into dimethylamine after heating, which can deprotonate the organic carboxylic acid ligand, promote the dissolution of the ligand, and further form coordination with the metal defect site; then, a metal ligand titanium isopropoxide is added to the system, and at 80°C to 150°C, the titanium isopropoxide and the organic carboxylic acid ligand in-situ grow a metal organic framework material on the surface of the titanium material, and the titanium material loaded with the metal organic framework material coating is subjected to annealing carbonization and oxidation treatment to obtain a carbon-wrapped oxide coating on the surface of the titanium material. The coating prepared by the above method is tightly bonded to the titanium base material in the form of Ti—O covalent bonds, avoiding the shedding and cracking of the coating caused by the mismatch between the carbon layer and the base metal material, improving the bonding strength between the carbon layer and the base metal material, and the coating preparation method is simple, convenient and easy to implement.

[0024] The carbon coating and metal oxide prepared by the invention enable the coating to have both high conductivity and high corrosion resistance.

[0025] The coating prepared by the method of the present invention has the advantages of high coating, high uniformity and high bonding strength, and is low in cost, simple in operation and high in repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of the preparation principle of the carbon-coated titanium oxide coating on the surface of the titanium material of the present invention.

[0027] Figure 2 This is a scanning electron microscope (SEM) image of the surface of the carbon-wrapped titanium oxide coating material in Example 1.

[0028] Figure 3 This is a scanning electron microscope (SEM) image of the thickness cross section of the carbon-wrapped titanium oxide coating material in Example 1.

[0029] Figure 4 This is the full X-ray photoelectron spectrum XPS of the carbon-coated titanium oxide coating material in Example 1 and the narrow scan illustrations of C, Ti, and O elements.

[0030] Figure 5In the figure, a is a physical picture of the carbon-wrapped titanium oxide coating material after the adhesion cross-cut test in Example 1, and b is a tape adhesion picture; c is a physical picture of the carbon-wrapped titanium oxide coating material after the adhesion cross-cut test in Comparative Example 1, and d is a tape adhesion picture; e is a physical picture of the carbon-wrapped titanium oxide coating material after the adhesion cross-cut test in Comparative Example 2, and f is a tape adhesion picture.

[0031] Figure 6 This is a polarization curve test diagram of the carbon-wrapped titanium oxide coating material in the anode working environment simulated in the PEMWE device in Example 1.

[0032] Figure 7 This is a surface contact resistance diagram of the carbon-wrapped titanium oxide coating material after 24h-2V constant potential polarization test in Example 1.

[0033] Figure 8 This is a polarization curve test diagram of the carbon-wrapped titanium oxide coating material in the anode working environment simulated in the PEMFC device in Example 1.

[0034] Fig. 9 This is a surface contact resistance diagram of the carbon-wrapped titanium oxide coating material after 24h-0.8V constant potential polarization test in Example 1. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.

[0036] The present invention provides a method for preparing a carbon-wrapped oxide coating on the surface of a titanium material, comprising the following steps:

[0037] (1) The titanium material is treated with an inorganic acid to obtain a defect-rich titanium material.

[0038] It should be noted that when the titanium material is immersed in an inorganic acid solution, titanium generates metal cations under acidic conditions, which makes the surface of the titanium material have highly reactive defect sites.

[0039] (2) The organic carboxylic acid ligand, anhydrous methanol and N,N-dimethylformamide are uniformly mixed and added to the defect-rich titanium material for adsorption, so that the organic carboxylic acid ligand forms a Ti-O ionic bond with the defect sites in the titanium material.

[0040] It should be noted that anhydrous methanol and N, N-dimethylformamide act as solvents. The reason for choosing this solvent is that anhydrous methanol can stabilize the organic carboxylic acid ligands and regulate the balance between nucleation and growth of metal organic frameworks. N, N-dimethylformamide decomposes into dimethylamine after heating, which can deprotonate the organic carboxylic acid ligands, promote the dissolution of the ligands, and further bind to the Ti at the metal defect sites. 3+ Form coordination.

[0041] Organic carboxylic acid ligands are precursors for the generation of metal-organic framework materials. They are first coordinated with defect sites in titanium materials to form Ti-O ionic bonds, thereby improving the bonding strength between the subsequently generated coating and the titanium material substrate.

[0042] In a preferred embodiment of the present invention, the organic carboxylic acid ligand may be one of terephthalic acid, 2-aminoterephthalic acid, 2,5-dihydroxyterephthalic acid and 3,3',5,5'-tetracarboxydiphenylmethane.

[0043] (3) Then, a metal ligand titanium isopropoxide is added to the system and reacted at 80°C to 150°C. During the reaction, titanium isopropoxide and organic carboxylic acid ligands grow in situ on the surface of the titanium material, and the titanium metal ion center and the bridging organic ligands are interconnected through self-assembly to form an organic-inorganic hybrid metal-organic framework material, thereby obtaining a titanium material loaded with a metal-organic framework material coating.

[0044] It should be noted that titanium isopropoxide is selected as the metal ligand because: titanium isopropoxide is soluble in organic solvents, is resistant to acid and oxidation at room temperature, has stable chemical properties, and as a metal ion source, it continuously coordinates and polymerizes with the precursor carboxylic acid in the solution through self-assembly to form a metal organic framework material coating.

[0045] (4) The titanium material loaded with the metal organic framework material coating is subjected to annealing, carbonization and oxidation treatment to obtain a carbon-coated oxide coating on the surface of the titanium material.

[0046] It should be noted that the carbon-wrapped oxide coating here refers to the titanium ions in the center of the metal ions reacting with oxygen to form titanium oxide. The organic ligands in the metal organic framework material are carbonized at high temperature, and the titanium oxide is wrapped in a carbon layer to form a coating material, which is loaded on the titanium material substrate. The coating has high conductivity and high corrosion resistance, and is tightly bonded to the titanium substrate material in the form of Ti-O covalent bonds, avoiding the shedding and cracking of the coating caused by the mismatch between the carbon layer and the base metal material, and improving the bonding strength between the carbon layer and the base metal material.

[0047] In a preferred embodiment of the present invention, the annealing, carbonization and oxidation are carried out in a muffle furnace in an air atmosphere at a temperature of 200° C. to 800° C. and a holding time of 10 min to 120 min.

[0048] The present invention will be specifically described below by the following examples.

[0049] Example 1

[0050] A method for obtaining a carbon-wrapped titanium oxide coated titanium sheet by loading a metal organic framework MIL-125-NH2 as a precursor, the specific steps being:

[0051] (1) Anhydrous oxalic acid is added to pure water and stirred to dissolve to form a 10 wt % oxalic acid solution. After heating to 80° C., a titanium plate is immersed in the oxalic acid solution for 10 min, then taken out and rinsed with ultrapure water to obtain a defect-rich titanium plate.

[0052] (2) 2-aminoterephthalic acid (NH2-BDC), anhydrous methanol (MeOH) and 40 mL N, N-dimethylformamide (DMF) were mixed in a molar ratio of 1:15:30 to form a mixed solution, and stirred at room temperature until NH2-BDC was fully dissolved. Then, the defect-rich titanium plate of step (1) was added to the mixed solution and stirred for 24 hours.

[0053] (3) Adding metal ligand titanium isopropoxide (Ti(OCH(CH3)2)4) in an amount equimolar to NH2-BDC to the mixed solution and titanium sheet of step (2), heating to 120°C and reflux for 24 hours, taking out the titanium sheet after cooling to room temperature, rinsing with deionized water, and then drying in an oven at 80°C to obtain a titanium sheet coated with a metal organic framework MIL-125-NH2 material.

[0054] (4) The titanium sheet coated with the metal organic framework MIL-125-NH2 material described in step (3) is subjected to annealing, carbonization and oxidation treatment in a muffle furnace, the temperature is increased to 600° C. at 5° C. / min and maintained for 30 min, and then cooled to room temperature to obtain a titanium sheet of carbon-encapsulated titanium oxide coating material.

[0055] Comparative Example 1

[0056] A method for obtaining a carbon-wrapped titanium oxide coated titanium sheet by using a metal organic framework MIL-125-NH2 as a precursor by electrostatic adsorption, the specific steps are as follows:

[0057] (1) Use acetone, ethanol and water to rinse the titanium plate in turn to clean the surface, remove oil and dust.

[0058] (2) 2-aminoterephthalic acid (NH2-BDC), anhydrous methanol (MeOH) and 40 mL N, N-dimethylformamide (DMF) were mixed in a molar ratio of 1:15:30 to form a mixed solution, and stirred at room temperature until NH2-BDC was fully dissolved. Then, the titanium plate of step (1) was added to the mixed solution, and stirred for electrostatic adsorption for 24 hours.

[0059] (3) Adding metal ligand titanium isopropoxide (Ti(OCH(CH3)2)4) in an amount equimolar to NH2-BDC to the mixed solution and titanium sheet of step (2), heating to 120°C and reflux for 24 hours, taking out the titanium sheet after cooling to room temperature, rinsing with deionized water, and then drying in an oven at 80°C to obtain a titanium sheet coated with a metal organic framework MIL-125-NH2 material.

[0060] (4) The titanium sheet coated with the metal organic framework MIL-125-NH2 material described in step (3) is subjected to annealing, carbonization and oxidation treatment in a muffle furnace, the temperature is increased to 600° C. at 5° C. / min and maintained for 30 min, and then cooled to room temperature to obtain a titanium sheet of carbon-encapsulated titanium oxide coating material.

[0061] Comparative Example 2

[0062] A method for obtaining a carbon-wrapped titanium oxide coated titanium sheet by directly sputtering carbon and titanium oxide materials through physical vapor deposition magnetron sputtering technology, the specific steps are:

[0063] (1) Use acetone, ethanol and water to rinse the titanium plate in turn to clean the surface, remove oil and dust.

[0064] (2) The titanium plate is placed in a magnetron sputtering chamber, carbon is used as a sputtering target, Ar is used as a working gas, the gas flow rate is set to 30 sccm, the chamber temperature is 150°C, the sputtering pressure is 1 Pa, the power is 400 W, the bias voltage is 60 V, and the sputtering time is 300 s. A titanium plate with a carbon coating material is obtained.

[0065] (3) The carbon-coated titanium plate obtained in step (2) is placed in a magnetron sputtering chamber, and carbon and titanium oxide are used as sputtering targets for simultaneous sputtering. Ar is used as the working gas, and the gas flow rate is set to 30 sccm, the chamber temperature is 150° C., the sputtering pressure is 1 Pa, the carbon target power is 400 W, the titanium oxide target power is 200 W, the bias voltage is 60 V, and the sputtering time is 300 s to obtain a titanium plate of carbon composite titanium oxide coating material.

[0066] (4) The titanium plate of the carbon-composite titanium oxide coating material obtained in step (3) is placed in a magnetron sputtering chamber, and carbon is used as a sputtering target for sputtering. Ar is used as the working gas, and the gas flow rate is set to 30 sccm, the chamber temperature is 150° C., the sputtering pressure is 1 Pa, the carbon target power is 400 W, the bias voltage is 60 V, and the sputtering time is 300 s to obtain a titanium plate of the carbon-composite titanium oxide coating material.

[0067] The titanium sheet of the carbon-coated titanium oxide coating material obtained in step (4) of Example 1 was characterized by scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS), and the Figure 2 , Figure 3 and Figure 4 .from Figure 2 It can be seen that the obtained carbon-wrapped titanium oxide coating material is uniform and dense on the surface of the titanium plate. Figure 3 It can be seen that the thickness of the coating is about 200nm. Figure 4 It can be seen that the coating element composition obviously contains Ti, C, and O elements. Ti comes from the substrate and titanium oxide, C comes from the carbon layer formed by carbonization of the MOF material, and O comes from titanium oxide particles formed by oxidation reaction between MOF and oxygen in the air and metal Ti ions in the MOF material.

[0068] The titanium sheet of the carbon-coated titanium oxide coating material obtained in Example 1 was subjected to a cross-cut test, also known as a "tape test", to measure the adhesion strength of the coating. Figure 5 In a, use a sharp tool to cross-hatch the coated titanium material, then firmly stick the special 3M tape on the test area and then tear it off. Compare the cross-hatch test area with the ISO 2409:1992 adhesion standard. Figure 5 As can be seen in b, after the tape was removed, the cut edge was almost smooth without any falling off. The results show that the prepared carbon-encapsulated titanium oxide coating has good adhesion and meets the ISO Class 0 standard.

[0069] The titanium sheet of the carbon-coated titanium oxide coating material obtained in Comparative Example 1 was subjected to a cross-cut test. Figure 5 In c, use a sharp tool to cross-hatch the coated titanium material, then firmly stick the special 3M tape on the test area and then tear it off. Compare the cross-hatch test area with the ISO 2409:1992 adhesion standard. Figure 5 As can be seen in middle d, after the tape was removed, large fragments of the coating fell off along the cut edge and some grids fell off completely, with the affected area being greater than 65%. The results show that the prepared carbon-encapsulated titanium oxide coating has extremely poor adhesion, belonging to the ISO Class 5 standard.

[0070] The titanium sheet of the carbon-coated titanium oxide coating material obtained in Comparative Example 2 was subjected to a cross-cut test. Figure 5In the middle, use a sharp tool to cross-hatch the coated titanium material, then firmly stick the special 3M tape on the test area and then tear it off. Compare the cross-hatch test area with the ISO 2409:1992 adhesion standard. Figure 5 As can be seen in Figure f, there is slight peeling after the tape is removed, and the affected cut grid area is greater than 5% but less than 15%. The results show that the prepared carbon-wrapped titanium oxide coating has poor adhesion and belongs to the ISO Class 2 standard.

[0071] At 80°C and with 20 sccm H2 continuously flowing, a corrosive acid solution (0.5 M H2SO4 and 5 ppm F - ) was used as electrolyte to simulate the working environment of the anode bipolar plate and diffusion layer in the proton exchange membrane water electrolysis (PEMWE) device, and a three-electrode system (Ag / AgCl as reference electrode and platinum as counter electrode) was used to perform a potentiodynamic polarization (Tafel) test (polarization voltage was -0.6 to 2 V) on the titanium sheet of the carbon-wrapped titanium oxide coating material obtained in step (4) of Example 1, and the result was Figure 6 .from Figure 6 It can be seen that the self-corrosion potential of pure titanium plate is -0.33V, and the corrosion current density under the self-corrosion potential is 9.88μA·cm 2 The self-corrosion potential of the titanium sheet with carbon-coated titanium oxide coating material is -0.22V, and the corrosion current density at the self-corrosion potential is 0.75μA·cm 2 The carbon-wrapped titanium oxide coating has better corrosion resistance. Under the same simulation conditions, the titanium sheet of the carbon-wrapped titanium oxide coating material was subjected to 24h constant potential polarization (IT) (constant voltage of 2V) to simulate the life test. The surface contact resistance (ICR) of the titanium sheet after constant potential polarization was tested, and the results were Figure 7 .from Figure 7 It can be seen that at 1.5MPa, the surface contact resistance of the pure titanium plate is 14.02mΩ·cm 2 After coating with carbon-wrapped titanium oxide coating, the surface contact resistance is significantly reduced to 5.91mΩ·cm 2 After 24 hours of constant potential polarization, the surface contact resistance of the material is 6.10 mΩ·cm 2 , almost unchanged, still meets the U.S. Department of Energy (DOE) 2020 bipolar plate surface contact resistance <10mΩ·cm 2 The technical indicators show that the prepared carbon-wrapped titanium oxide coating has better electrical conductivity and meets the service requirements of the anode bipolar plate and diffusion layer in the proton exchange membrane water electrolysis (PEMWE) equipment.

[0072] At 80°C and with 20 sccm H2 flowing continuously, a corrosive acid solution (0.5 mM H2SO4 and 5 ppm F - ) was used as electrolyte to simulate the working environment of the anode bipolar plate and diffusion layer in a hydrogen fuel cell (PEMFC) device. A three-electrode system (Ag / AgCl as reference electrode and platinum as counter electrode) was used to perform a potentiodynamic polarization (Tafel) test (polarization voltage was -0.5 to 1.6 V) on the titanium sheet of the carbon-wrapped titanium oxide coating material obtained in step (4) of Example 1 to obtain Figure 8 .from Figure 8 It can be seen that the self-corrosion potential of pure titanium plate is -0.33V, and the corrosion current density under the self-corrosion potential is 9.88μA·cm 2 The self-corrosion potential of the titanium sheet with carbon-coated titanium oxide coating material is -0.11V, and the corrosion current density at the self-corrosion potential is 0.08μA·cm 2 The carbon-coated titanium oxide coating has better corrosion resistance. Under the same simulation conditions, the titanium sheet of the carbon-coated titanium oxide coating material was subjected to constant potential polarization (IT) (constant voltage of 0.8V) for 24 hours to simulate the life test. The surface contact resistance (ICR) of the titanium sheet after constant potential polarization was tested to obtain Fig. 9 .from Fig. 9 It can be seen that at 1.5MPa, the surface contact resistance of the pure titanium plate is 14.02mΩ·cm 2 After coating with carbon-wrapped titanium oxide coating, the surface contact resistance is significantly reduced to 5.91mΩ·cm 2 After 24 hours of constant potential polarization, the surface contact resistance of the material is 5.96 mΩ·cm 2 The surface contact resistance after constant potential polarization is still lower than the surface contact resistance of DOE bipolar plate by 10mΩ·cm 2 The technical indicators show that the carbon-wrapped titanium oxide coating also has better electrical conductivity and meets the service requirements of the anode bipolar plate and diffusion layer in hydrogen fuel cell (PEMFC) equipment.

[0073] Example 2

[0074] A method for obtaining a carbon-wrapped titanium oxide coated titanium sheet by loading a metal organic framework MIL-125-NH2 as a precursor, the specific steps being:

[0075] (1) Anhydrous oxalic acid is added to pure water and stirred to dissolve to form a 10 wt % oxalic acid solution. After heating to 80° C., a titanium plate is immersed in the oxalic acid solution for 10 min, then taken out and rinsed with ultrapure water to obtain a defect-rich titanium plate.

[0076] (2) 2-aminoterephthalic acid (NH2-BDC), anhydrous methanol (MeOH) and 40 mL N, N-dimethylformamide (DMF) were mixed in a molar ratio of 1:15:30 to form a mixed solution, and stirred at room temperature until NH2-BDC was fully dissolved. Then, the defect-rich titanium plate of step (1) was added to the mixed solution and stirred for 24 hours.

[0077] (3) Adding metal ligand titanium isopropoxide (Ti(OCH(CH3)2)4) to the mixed solution and titanium sheet in step (2) in a molar ratio of titanium isopropoxide to NH2-BDC of 0.5:1, and heating to 120°C for reflux for 24 hours. After cooling to room temperature, taking out the titanium sheet, rinsing it with deionized water, and then drying it in an oven at 80°C to obtain a titanium sheet coated with a metal organic framework MIL-125-NH2 material.

[0078] (4) The titanium sheet coated with the metal organic framework MIL-125-NH2 material described in step (3) is subjected to annealing, carbonization and oxidation treatment in a muffle furnace, the temperature is increased to 600° C. at 5° C. / min and maintained for 30 min, and then cooled to room temperature to obtain a titanium sheet of carbon-encapsulated titanium oxide coating material.

[0079] Example 3

[0080] A method for obtaining a carbon-wrapped titanium oxide coated titanium sheet by loading a metal organic framework MIL-125-NH2 as a precursor, the specific steps being:

[0081] (1) Anhydrous oxalic acid is added to pure water and stirred to dissolve to form a 10 wt % oxalic acid solution. After heating to 80° C., a titanium plate is immersed in the oxalic acid solution for 10 min, then taken out and rinsed with ultrapure water to obtain a defect-rich titanium plate.

[0082] (2) 2-aminoterephthalic acid (NH2-BDC), anhydrous methanol (MeOH) and 40 mL N, N-dimethylformamide (DMF) were mixed in a molar ratio of 1:15:30 to form a mixed solution, and stirred at room temperature until NH2-BDC was fully dissolved. Then, the defect-rich titanium plate of step (1) was added to the mixed solution and stirred for 24 hours.

[0083] (3) Adding metal ligand titanium isopropoxide (Ti(OCH(CH3)2)4) in an amount equimolar to NH2-BDC to the mixed solution and titanium plate of step (2), heating to 80°C and reflux for 24 hours, taking out the titanium plate after cooling to room temperature, rinsing with deionized water, and then drying in an oven at 80°C to obtain a titanium plate coated with a metal organic framework MIL-125-NH2 material.

[0084] (4) The titanium sheet coated with the metal organic framework MIL-125-NH2 material described in step (3) is subjected to annealing, carbonization and oxidation treatment in a muffle furnace, the temperature is increased to 600° C. at 5° C. / min and maintained for 30 min, and then cooled to room temperature to obtain a titanium sheet of carbon-encapsulated titanium oxide coating material.

[0085] Example 4

[0086] A method for obtaining a carbon-wrapped titanium oxide coated titanium sheet by loading a metal organic framework MIL-125-NH2 as a precursor, the specific steps being:

[0087] (1) Anhydrous oxalic acid is added to pure water and stirred to dissolve to form a 10 wt % oxalic acid solution. After heating to 80° C., a titanium plate is immersed in the oxalic acid solution for 10 min, then taken out and rinsed with ultrapure water to obtain a defect-rich titanium plate.

[0088] (2) 2-aminoterephthalic acid (NH2-BDC), anhydrous methanol (MeOH) and 40 mL N, N-dimethylformamide (DMF) were mixed in a molar ratio of 1:15:30 to form a mixed solution, and stirred at room temperature until NH2-BDC was fully dissolved. Then, the defect-rich titanium plate of step (1) was added to the mixed solution and stirred for 24 hours.

[0089] (3) Adding metal ligand titanium isopropoxide (Ti(OCH(CH3)2)4) in an amount equal to the molar amount of NH2-BDC to the mixed solution and titanium plate in step (2), heating to 100°C and reflux for 24 hours, cooling to room temperature, taking out the titanium plate, rinsing it with deionized water, and then drying it in an oven at 80°C to obtain a titanium plate coated with a metal organic framework MIL-125-NH2 material.

[0090] (4) The titanium sheet coated with the metal organic framework MIL-125-NH2 material described in step (3) is subjected to annealing, carbonization and oxidation treatment in a muffle furnace, the temperature is increased to 600° C. at 5° C. / min and maintained for 30 min, and then cooled to room temperature to obtain a titanium sheet of carbon-encapsulated titanium oxide coating material.

[0091] Example 5

[0092] A method for obtaining carbon-wrapped titanium oxide coated titanium fiber felt by loading a metal organic framework MIL-125 as a precursor, the specific steps are:

[0093] (1) Add 10 g of anhydrous oxalic acid into 100 ml of water and stir to dissolve to form a 10 wt% oxalic acid solution. After heating to 80°C, soak a titanium fiber felt having a length of 20 mm, a width of 10 mm, and a thickness of 1 mm in the oxalic acid solution for 10 min. After taking it out, rinse it with ultrapure water to obtain a defect-rich titanium fiber felt.

[0094] (2) Add 2.5 g of terephthalic acid (BDC) to a beaker containing a mixed solution of 10 mL of anhydrous methanol (MeOH) and 40 mL of N,N-dimethylformamide (DMF), and stir at room temperature until BDC is fully dissolved. Then, add the defect-rich titanium fiber felt of step (1) to the mixed solution and stir and adsorb for 24 hours.

[0095] (3) Continue to add 2.5 mL of the metal ligand titanium isopropoxide to the mixed solution and titanium fiber felt in step (2), heat to 120° C. and reflux for 24 hours. After cooling to room temperature, take out the titanium fiber felt, rinse it with deionized water, and then dry it in an oven at 80° C. to obtain a titanium fiber felt coated with a metal organic framework MIL-125 material.

[0096] (4) The titanium fiber felt loaded with the metal organic framework MIL-125 material coating described in step (3) is subjected to annealing carbonization and oxidation treatment in a muffle furnace, the temperature is increased to 600° C. at 5° C. / min and maintained for 30 min, and then cooled to room temperature to obtain the titanium fiber felt with carbon-encapsulated titanium oxide coating material.

[0097] Example 6

[0098] A method for obtaining a carbon-wrapped titanium oxide coated titanium rod by loading a metal organic framework MIL-167 as a precursor, the specific steps are:

[0099] (1) 10 g of anhydrous oxalic acid was added to 100 ml of water and stirred to dissolve to form a 10 wt% oxalic acid solution. After heating to 80° C., a titanium rod with a diameter of 10 mm and a length of 20 mm was immersed in the oxalic acid solution for 10 min. After being taken out, it was rinsed with ultrapure water to obtain a defect-rich titanium rod.

[0100] (2) Add 2.65 g of 2,5-dihydroxyterephthalic acid (DHTA) to a beaker containing a mixed solution of 10 mL of anhydrous methanol (MeOH) and 40 mL of N,N-dimethylformamide (DMF), and stir at room temperature until DHTA is fully dissolved. Then, add the defect-rich titanium rod from step (1) to the mixed solution and stir and adsorb for 24 hours.

[0101] (3) Add 2.65 mL of the metal ligand titanium isopropoxide to the mixed solution and titanium rod in step (2), heat to 150° C. and reflux for 48 h. After cooling to room temperature, take out the titanium rod, rinse it with deionized water, and then dry it in an oven at 80° C. to obtain a titanium rod coated with a metal organic framework MIL-167 material.

[0102] (4) The titanium rod coated with the metal organic framework MIL-167 material described in step (3) is subjected to annealing, carbonization and oxidation treatment in a muffle furnace, the temperature is increased to 600° C. at 5° C. / min and maintained for 30 min, and then cooled to room temperature to obtain a titanium rod with a carbon-coated titanium oxide coating material.

[0103] Example 7

[0104] A method for obtaining a carbon-wrapped titanium oxide coated titanium sheet by loading a metal organic framework MIL-177 as a precursor, the specific steps being:

[0105] (1) 10 g of anhydrous oxalic acid was added to 100 ml of water and stirred to dissolve to form a 10 wt% oxalic acid solution. After heating to 80° C., a titanium plate with a length of 10 mm, a width of 10 mm, and a thickness of 1 mm was immersed in the oxalic acid solution for 10 min. After being taken out, it was rinsed with ultrapure water to obtain a defect-rich titanium plate.

[0106] (2) Add 2.5 g of 3,3',5,5'-tetracarboxy diphenylmethane (PCN-12) to a beaker containing a mixed solution of 10 mL of anhydrous methanol (MeOH) and 40 mL of N,N-dimethylformamide (DMF), and stir at room temperature until PCN-12 is fully dissolved. Then, add the defect-rich titanium plate of step (1) to the mixed solution and stir and adsorb for 24 h.

[0107] (3) Add 2.5 mL of the metal ligand titanium isopropoxide to the mixed solution and the titanium plate in step (2), heat to 150° C. and reflux for 72 h. After cooling to room temperature, take out the titanium plate, rinse it with deionized water, and then dry it in an oven at 80° C. to obtain a titanium plate coated with a metal organic framework MIL-177 material.

[0108] (4) The titanium sheet loaded with the metal organic framework MIL-177 material coating described in step (3) is subjected to annealing, carbonization and oxidation treatment in a muffle furnace, the temperature is increased to 600° C. at a rate of 5° C. / min and maintained for 30 min, and then cooled to room temperature to obtain a titanium sheet of carbon-encapsulated titanium oxide coating material.

[0109] The material properties prepared in Examples 2 to 7 are similar to those in Example 1 and are not described in detail here.

[0110] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.

Claims

1. A method for preparing a carbon-coated oxide coating on the surface of a titanium material, characterized in that: The following steps are involved: Treating the titanium material with an inorganic acid solution to obtain a defect-rich titanium material; The organic carboxylic acid ligand, anhydrous methanol and N,N-dimethylformamide are uniformly mixed, and added to the defect-rich titanium material for adsorption, so that the organic carboxylic acid ligand forms a Ti-O ionic bond with the defect sites in the titanium material; Then, a metal ligand titanium isopropoxide is added to the system and reacted at 80°C to 150°C. During the reaction, titanium isopropoxide and organic carboxylic acid ligands in situ grow metal organic framework materials on the surface of the titanium material to form a titanium material loaded with a metal organic framework material coating; The titanium material loaded with the metal organic framework material coating is subjected to annealing, carbonization and oxidation treatment to obtain a carbon-wrapped oxide coating on the surface of the titanium material.

2. The preparation method according to claim 1, characterized in that: The organic carboxylic acid ligand is one of terephthalic acid, 2-aminoterephthalic acid, 2,5-dihydroxyterephthalic acid and 3,3',5,5'-tetracarboxy diphenylmethane.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the organic carboxylic acid ligand, anhydrous methanol and N,N-dimethylformamide is 1:10-20:20-40.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the metal ligand titanium isopropoxide to the organic carboxylic acid ligand is 0.5-1:

1.

5. The preparation method according to claim 1, characterized in that: The reaction time is 10h~100h.

6. The preparation method according to claim 1, characterized in that: Annealing, carbonization and oxidation treatment are carried out in a muffle furnace in an air atmosphere at a temperature of 200°C to 800°C and a holding time of 10min to 120min.

7. The preparation method according to claim 1, characterized in that: The titanium material is immersed in an inorganic acid solution and then rinsed with water to obtain a defect-rich titanium material; the temperature is 70° C. to 100° C. and the immersion time is 1 min to 30 min.

8. The preparation method according to claim 1, characterized in that: The inorganic acid solution is selected from one of hydrochloric acid with a concentration of 0.5wt%, sulfuric acid with a concentration of 5wt%, phosphoric acid with a concentration of 85wt%, hydrofluoric acid with a concentration of 5wt% and oxalic acid with a concentration of 5wt% to 20wt%.

9. A carbon-coated oxide coating on the surface of a titanium material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the carbon-wrapped oxide coating on the surface of the titanium material according to claim 9 in the protection of proton exchange membrane water electrolysis or hydrogen fuel cell equipment.

Citation Information

Patent Citations

  • Method of forming oxide based nano structures

    CN101219777A

  • Fuel cell bipolar plate with corrosion-resistant passivation coating and preparation method of fuel cell bipolar plate

    CN116936839A

  • Organic network structure and method for manufacturing the same

    KR1020150138750A

  • Electrode material for lithium and lithium ion batteries

    WO2012163426A1